2018
DOI: 10.1038/s41598-018-28070-0
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B is elevated in autoimmune blistering diseases and cleaves key anchoring proteins of the dermal-epidermal junction

Abstract: In healthy skin, epidermis and dermis are anchored together at the dermal-epidermal junction (DEJ), a specialized basement membrane pivotal for skin integrity and function. However, increased inflammation in the DEJ is associated with the disruption and separation of this junction and sub-epidermal blistering. Granzyme B (GzmB) is a serine protease secreted by immune cells. Dysregulated inflammation may lead to increased GzmB accumulation and proteolysis in the extracellular milieu. Although elevated GzmB is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 71 publications
2
34
0
Order By: Relevance
“…Densitometric analysis revealed that the cleaved bands for FN and LAM-5 reached significance (p < 0.05), while that of COL-IV did not (p > 0.05) (Figures 8D-F). There were no cleaved bands observed for COL-I ( Supplementary Figure 2), consistent with the earlier finding that COL-1 is not a substrate of GzmB (15,16).…”
Section: Extracellular Gzmb Degrades Primary Rpe-derived Ecm Proteinssupporting
confidence: 91%
See 1 more Smart Citation
“…Densitometric analysis revealed that the cleaved bands for FN and LAM-5 reached significance (p < 0.05), while that of COL-IV did not (p > 0.05) (Figures 8D-F). There were no cleaved bands observed for COL-I ( Supplementary Figure 2), consistent with the earlier finding that COL-1 is not a substrate of GzmB (15,16).…”
Section: Extracellular Gzmb Degrades Primary Rpe-derived Ecm Proteinssupporting
confidence: 91%
“…BM is an important outer retinal ECM that regulates the exchange between the (1) metabolically active combination of photoreceptor and RPE and (2) the choriocapillaris blood supply. Several of the ECM proteins within BM are known substrates for extracellular GzmB activity, including fibronectin (FN), vitronectin (VN), and laminin (LAM) and a small subset of collagens (COL) (1,(15)(16)(17)(18) (Figure 1). The remodeling of BM during aging and AMD is known to also affect RPE cell adhesion and function, which in turn, compromises oBRB function (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Acta Dermato-Venereologica 105 Collagen XVII processing and blistering skin diseases Theme issue: Blistering skin disorders in infiltrated cells in BP lesional skin and that not only does this enzyme cleave COL17, but it also cleaves other molecules present at the DEJ, including α6/β4 integrins and collagen VII (29).…”
Section: Advances In Dermatology and Venereologymentioning
confidence: 99%
“…Cathepsins and caspases can cleave ECM and the cytoskeleton and thus relate to our proteomics findings in AMR, [41][42][43] whereas granzymes are mainly expressed by immune cells. 44,45 We next used MEROPS 46 to identify proteases predicted to cleave the ECM proteins in each AMR compartment. CTSL, CTSS, and CTSV were the top 3 proteases expressed in the kidney and predicted to cleave the highest number of ECM proteins dysregulated in the AMR glomeruli ( Fig.6C).…”
Section: Galectin-1 and Cathepsins Are Linked To Ecm Alterations In Amrmentioning
confidence: 99%